RETRACTED: Enhanced AC133-specific CAR T cell therapy induces durable remissions in mice with metastatic small cell lung cancer. (1st November 2021) - Taromi, Sanaz; Firat, Elke; Simonis, Alexander; Braun, Lukas M.; Apostolova, Petya; Elze, Mirjam; Passlick, Bernward; Schumacher, Alicia; Lagies, Simon; Frey, Anna; Schmitt-Graeff, Annette; Burger, Meike; et al.
Abstract : This article has been retracted: please see Elsevier Policy on Article Withdrawal (https://www.elsevier.com/about/our-business/policies/article-withdrawal ). This article has been retracted at the request of the Editor-in-Chief. Following the publication of the above article, the Editor was notified that an error occurred in which all images were published with incorrect versions. The Editor has taken the decision that the manuscript is no longer acceptable in its current form, nor with a corrigendum, as the extensive changes to the figures and publication would lead to ambiguity for our readers. We have therefore made the decision to retract this manuscript from Cancer Letters with the possibility of resubmission and republication of the manuscript in its corrected form after peer review.